Pelaksanaan Pengurusan Kualiti Menyeluruh (TQM) Di Daerah Kuala Muda Ke Arah Mencapai ISO 9002 Menjamin Kepuasan Bekerja Guru-guru - Ghazali, Ismail (2001)
The objective of research is to measure the overall level of job satisfaction amongst secondary school teachers in the Kuala Muda district after the implementation of TQM toward achieving the MS IS0 9002 certificate. To this end, important factors such as sex, age, duration of service, salary and allowances, workplace condition, training and recognition, colleagues and quality management which are related to job satisfaction amongst teachers in the district are taken into consideration. The research is camed out by way of data collection based on questionaires on 160 secondary school teachers from the Kuala Muda district. This type of research was known as "organisational climate description". T - test and one way ANOVA have been used to test differences and the Pearson "r" Test to test correlation. All statistic test are done at equation (significant) level p < 0.05. The research shows that the duration of service and the differences in age do have any vital influence on job satisfaction amongst teachers in the Kuala Muda district. In essence, it does not follow that the longer the duration of service or the older a teacher is, the higher the level ofjob satisfaction is. The research also implicates that workplace environment plays only a mediocre role towards influencing the level of job satisfaction; the correlation being 0.452. However, this research reveals quite a different factor which has a significant influence on job satisfaction i.e gender. It is found that lady teachers have higher level of job satisfaction compared to man teachers after the implementation of TQM in Kuala Muda district schools. Factors such as colleagues, training and recognition relate significantly to the level of job satisfaction. On average, 92.4 % of the teachers agree that they maintain a good professional relationship with their colleagues in their respective organisations. Quality management is found to have a vital influence on the level of job satisfaction. Generally, the research shows that 87.8 % of quality culture influences the level of job satisfaction among teachers in the Kuala Muda district, followed by 85.0 % of quality assurance and quality improvement.